Soft see-saw: Radiative origin of neutrino masses in SUSY theories - Luka Megrelidze; Zurab Tavartkiladze (Nuclear Physics B, 2017)
Radiative neutrino mass generation within supersymmetric (SUSY) construction is studied. The mechanism is considered where the lepton number violation is originating from the soft SUSY breaking terms. This requires MSSM extensions with states around the TeV scale. We present several explicit realizations based on extensions either by MSSM singlet or SU(2)w triplet states. Besides some novelties of the proposed scenarios, various phenomenological implications are also discussed.